2010
DOI: 10.4317/jced.2.e88
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol granuloma in the wall of a mandibular dentigerous cyst: a rare case report

Abstract: Cholesterol granuloma is an inflammatory reaction to cholesterol crystals deposition. It may develop in a variety of sites including the middle ear, mastoid process or even paranasal sinuses. Very few cases of cholesterol granuloma occurring in the jaws were reported. This report presents a rare case of cholesterol granuloma that developed in the wall of a large mandibular dentigerous cyst. The condition was treated with hemimandibulectomy followed by reconstruction with a free fibular flap. (10033290) Lee JH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 8 publications
(5 reference statements)
0
3
0
Order By: Relevance
“…Here, we present a rare case of CG in the wall of a dentigerous cyst associated with an impacted molar and involving the maxillary sinus. To the best of our knowledge, there are 12 published articles, and a comprehensive review of the scientific literature on this topic was conducted, encompassing relevant publications from 1984 to the present [1][2][3][4][6][7][8][9][10][11][12][13]. Furthermore, aside from our reported case, instances of CG in the oral cavity have been documented to either arise from an odontogenic source or extend from the maxillary sinus, presenting as an isolated intra-oral swelling (Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we present a rare case of CG in the wall of a dentigerous cyst associated with an impacted molar and involving the maxillary sinus. To the best of our knowledge, there are 12 published articles, and a comprehensive review of the scientific literature on this topic was conducted, encompassing relevant publications from 1984 to the present [1][2][3][4][6][7][8][9][10][11][12][13]. Furthermore, aside from our reported case, instances of CG in the oral cavity have been documented to either arise from an odontogenic source or extend from the maxillary sinus, presenting as an isolated intra-oral swelling (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Very few cases of CG of the jaw associated with the wall of dentigerous cysts have been reported to date [ 4 , 6 , 7 ]. Herein, we report the radiographic and histopathological features of a case of CG of the maxillary sinus that occurred in a dentigerous cyst.…”
Section: Introductionmentioning
confidence: 99%
“…CG histopathologically depicts a large collection of longitudinal cholesterol clefts that are formed at the site of cholesterol crystals because of dissolution of crystals at the time of tissue processing and is embedded in fibrous granulation tissue with surrounding foreign body type of multinucleated giant cells and macrophages filled with hemosiderin [4]. After an extensive survey, six cases of CG have been found in the oral cavity, in which only three cases of CG occurring in the wall of odontogenic cyst have been reported so far [37].…”
Section: Discussionmentioning
confidence: 99%
“…Hematoma from the mucosal bleeding would not be absorbed, resulting in its conversion to cholesterol crystals. However this cannot be a possible cause of CG occurring in the mandible due to the absence of intrabony cavities or drainage pathways [4]. …”
Section: Discussionmentioning
confidence: 99%
“…3 J H Lee et al first reported a case of cholesterol granuloma within a mandibular odontogenic cyst. 6 It can develop in a variety of body areas such as: the middle ear (most common site), mastoid process, testis, lungs, apex of temporal bone pyramid and paranasal sinuses. 7 Unlike cholesterol granuloma, development of ameloblastoma or even squamous cell carcinoma within dentigerous cysts have been previously reported.…”
Section: Cholesterol Granulomamentioning
confidence: 99%